An Associative Broadcast Based Coordination Model for Distributed Processes - Browne, James C.; Kane, Kevin; Tian, Hongxia (Coordination Models and Languages (COORDINATION 2002), 2002)
We define and describe a model for coordination of distributed processes or components based on associative broadcast. Associative broadcast encapsulates processes with an associative interface. The associative interface includes a profile, which specifies the current state of the component. Each message is sent with a conditional expression (selector), which evaluates to true for specific instances of profiles. Messages are broadcast but are received by only those processes where the selector of the message evaluates to true when matched with the profile of the component. Each component dynamically specifies its profile and selectors to conform to a coordination protocol. Components can, depending on their local state, enter or leave a coordinating set without affecting the other members of the set. Associative broadcast is defined and described. A formulation of associative broadcast implementing coordination among a dynamic set of distributed processes is defined and described. Distributed mutual exclusion is formulated in associative broadcast as an illustration.